2013
DOI: 10.1002/cmdc.201300134
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibitor Binding to the Papain‐Like Protease of Human SARS Coronavirus: Mechanistic and Inhibitor Design Implications

Abstract: We have previously developed two potent chemical classes that inhibit the essential papain-like protease (PLpro) of severe acute respiratory syndrome coronavirus (SARS-CoV). In this study, we applied a novel approach to identify small fragments that act synergistically with these inhibitors. A fragment library was screened in combination with four previously developed lead inhibitors by fluorescence-based enzymatic assays. Several fragment compounds synergistically enhanced the inhibitory activity of the lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
(37 reference statements)
0
19
1
Order By: Relevance
“…Mechanism of inhibition studies revealed that these compounds are mixed-type inhibitors with α values greater than 1, indicating that they bind to an allosteric site other than its catalytic site, but behave as if they are competitive inhibitors 35 . As noted above, these lead inhibitors bind to the flexible BL2 region and induce conformational changes to block substrate access to the catalytic site of the enzyme 27, 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism of inhibition studies revealed that these compounds are mixed-type inhibitors with α values greater than 1, indicating that they bind to an allosteric site other than its catalytic site, but behave as if they are competitive inhibitors 35 . As noted above, these lead inhibitors bind to the flexible BL2 region and induce conformational changes to block substrate access to the catalytic site of the enzyme 27, 28 .…”
Section: Resultsmentioning
confidence: 99%
“…GRL-0617, a highly effective SARS-CoV PL pro inhibitor whose binding site is in the S3-S4 site, also has a noncompetitive inhibition mechanism (Lee et al, 2013). As there are significant differences in the S3 subsite, as well as in the BL2 loop, between the SARS-CoV and MERS-CoV PL pro s, it is unlikely that GRL0617 and its derivatives will also inhibit MERS-CoV PL pro (Lei et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of PL pro in the maturation of the viral polyprotein and its role in counteracting cellular antiviral signaling pathways have contributed to its recognition as a promising target for therapeutic intervention, and the availability of X-ray crystallographic data [135,140], along with work describing the substrate specificity of PL pro at its cognate subsites [145,146], has contributed to such efforts. Highthroughput screening of small-molecule libraries and rational structure-guided design have led to the identification and development of several lead compounds capable of inhibiting the proteolytic activities of SARS-CoV PL pro [147][148][149][150][151][152][153][154].…”
Section: Sars-cov Pl Promentioning
confidence: 99%